2022
DOI: 10.1600/036364422x16442669847085
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Diversity and Taxonomic Importance of Fruits and Seeds of the Genus Spigelia (Loganiaceae) in Mexico

Abstract: Abstract— The genus Spigelia (Loganiaceae) is a Neotropical genus that includes more than 80 species distributed from the United States to Argentina. Systematic studies of the group have rarely considered the carpological characters, so their taxonomic importance has not been analyzed in detail. The aim of this study is to analyze the morphological characteristics of these organs to provide more information for a better species separation and for a more robust infra-generic classification. We provide a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…These characteristics, such as the presence of stipules or the phyllotaxis below the inflorescences, allow, in the absence of flowers, to approach to the identification of the species, which can be subsequently corroborated with the help of the diagnoses. Likewise, it has been observed that carpological characters present an important variation that allows the delimitation of species for their identification, even if the plant no longer has flowers or fruits (Islas-Hernández et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These characteristics, such as the presence of stipules or the phyllotaxis below the inflorescences, allow, in the absence of flowers, to approach to the identification of the species, which can be subsequently corroborated with the help of the diagnoses. Likewise, it has been observed that carpological characters present an important variation that allows the delimitation of species for their identification, even if the plant no longer has flowers or fruits (Islas-Hernández et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed knowledge of the morphological structures that help to identify the species (e.g., type of style, pollen, carpoatlas or shape of the seeds), can be integrated as morphological markers, which together with the molecular markers will allow in the future to generate combined phylogenetic analyzes (Peterson and Seberg, 1998). In this sense, the use of carpological characters for the separation of groups of species has been studied within the genus (Islas-Hernández et al, 2022), and this information will allow, together with the floral information, the proposal of new sections that have phylogenetic congruence (Gould, 1997) and that are complemented with information derived from the species of the SA region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations